The Concept of Social Philosophy by S.L. Frank. Experience of Comparative Analysis: G. Simmel, E. Husserl, M. Scheler - Alexander N. Malinkin (Социологический журнал, 2023)
The article is a continuation of the study of the evolution of social thought by S.L. Frank, the results of which began to be published in the previous issue. This article deals with the concept of social philosophy of S.L. Frank, set forth in his work “The Spiritual Foundations of Society”. The main ideas of his concept are compared to the views of G. Simmel, E. Husserl, M. Scheler. The author comes to the conclusion that Frank’s socio-philosophical doctrine is based on the idea of a “god-like” (“theomorphic”) person, who gradually overcomes his empirical, innate-animal nature in society and history and comes into his own as a person in pursuit of God — the highest foundation of the universe. The social and spiritual being merge, according to Frank, into one ontological unity, which is founded in the being of man — in the history of his society as a “phenomenology of the spirit” and “the dramatic fate of God in the heart of man”, as well as in his “living knowledge” about himself as a “medium”, “conduit” of higher principles and values. The concept of Frank’s social philosophy was formed, according to the author, under the influence of G. Simmel’s “philosophical sociology”, E. Husserl’s transcendental phenomenology, and his philosophical anthropology is in many ways close to Scheler’s early philosophical ideas.